THE ROLE OF BUSINESS JOURNALISM IN MODERN INTERNATIONAL BUSINESS - Poliakova Yuliia; Shayda Oksana; Stepanov Andriy (Херсонський державний університет, Видавничий дім «Гельветика», 2019)
The article is devoted to the study of the importance of business journalism for the development of international business in the global economy. The modern tendencies of the development of international business are systematised, and the significance and prospects for the use of business journalism tools are determined. The sectors producing the most popular business news are revealed. The functional purpose of the business press is considered in connection with forming the information environment of business development, and the main approaches to its classification are analysed. The role of business publications in advertising activity is estimated. The specific features and trends of the development of business publications in the modern global environment are singled out as well as the most common tools of corporate communication are identified. The transformation of business needs is considered in relation to the press, and the importance of business for the formation of the market of business publications is regarded.
РОЛЬ ДІЛОВОЇ ЖУРНАЛІСТИКИ У СУЧАСНОМУ МІЖНАРОДНОМУ БІЗНЕСІ
Keywords: international journalism; globalisation; international business; international communication; business press; advertising